Gluten - a nutritional enemy or indispensable diet ingredient? - Choina, Magdalena; Gromek, Weronika; Marzęda, Magdalena; Wilk, Klaudia; Łysiak, Katarzyna (Journal of Education, Health and Sport, 2022)
Introduction: Gluten is a mixture of wheat, rye and barley storage proteins. These corps have provided human beings worldwide with energy and nutrients for centuries. However, an increase in the occurrence of symptoms after the consumption of gluten has been observed recently. Although celiac disease is an indication of strict adherence to the gluten-free diet (GFD), the popularity of GFD is growing among healthy people. The risks of unsupported gluten elimination should be assessed before the introduction of GFD. Purpose: The study aims to define GFD and indicate who should follow the diet, as well as present difficulties concerning strict adherence to GFD and possible consequences of eliminating gluten on one’s own. Description of the state of knowledge: Regarding the mechanism, in which the symptoms after gluten consumption develop, the following diseases have been distinguished: celiac disease (CD), wheat allergy and non-celiac gluten sensitivity. Currently, the only indication of strict long-life adherence to GFD is CD. Such a restrictive approach may cause financial and social problems. Although the introduction of GFD improves the quality of life in CD patients, it does not lead to the immediate disappearance of the symptoms. Healthy people, who decide to eliminate gluten, should balance their diet carefully, as GFD might cause nutritional deficiencies and metabolic diseases. Summary: Strict long-life adherence to GFD is indicated in CD. This treatment may be problematic, which often is not evident to people who eliminate gluten on their own. Unbalanced GFD can lead to nutritional deficiencies as well as metabolic diseases.